The study to examine the impact of HRM practices on corporate performance in manufacturing firms in Guangdong Province, China - Zhongming, Xu; Marimuthu, Anbalagan (International Journal of Economics, Business and Management Studies, 2025)
This study investigates the relationship between key human resource management (HRM) practices namely procedural fairness, employee performance, information sharing, and organizational identity and corporate performance in Chinese manufacturing firms. The research adopts a quantitative approach, utilizing a self-administered, close-ended questionnaire to collect data from employees in two manufacturing firms located in Guangzhou, Guangdong Province, China. A probability-based stratified random sampling technique was employed to ensure a representative sample across different employee groups. The analysis tested nine hypotheses to examine the direct and indirect effects of HRM practices on corporate performance. The findings reveal that eight out of the nine proposed hypotheses were supported, indicating strong positive associations between the selected HRM practices and corporate performance. One exception emerged in the mediation analysis, suggesting that not all relationships are equally mediated by the proposed variables. These results underscore the strategic importance of implementing fair procedures, fostering open information sharing, enhancing employee performance, and strengthening organizational identity as pathways to improved corporate outcomes. The study provides practical insights for managers and policymakers in emerging and evolving industries, particularly in China, highlighting the need for integrated HRM strategies that align with broader organizational goals to sustain a competitive advantage in a dynamic business environment.